The Impact of The Tourism Sector and Original Regional Income on Gross Regional Domestic Product in East Java 1993-2022 - Librania Septa Monica Ambar Susanto; Ruth Eviana Hutabarat (CV. Ulil Albab Corp, 2024)
This journal examines whether there is an influence from the tourism sector and local revenue on gross regional domestic product in East Java. Using data from the Central Statistics Agency from 1993 to 2022, this research evaluates the direct impact of the tourism sector on the level of gross regional domestic product. The analytical method used is the multiple regression analysis method with five variables, namely the number of tourists, the number of tourism accommodation, the number of tourist attractions and income. regional origin and gross regional domestic product. From the research results, the number of tourists, number of tourist attractions and local revenue have an influence on gross regional domestic product, while the number of tourist accommodations has no influence on East Java's gross regional domestic product.